(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The relationship between politics and economics, how politics can affect the economy, and can they be distinguished from each other or not? The answers to these questions are presented in detail in the article.